Effect of Traditional Chinese Medicine on the Gut Microbiota in Heat-Stressed Laying Hens - Ye, Chunxin; Qu, Qian; Bai, Lin; Chen, Jiaxin; Cai, Zhuoke; Sun, Jiaqi; Liu, Cui; Shi, Dayou (Frontiers in Veterinary Science, 2022)
Gut microbiota plays an important role in health and disease. To determine whether the traditional Chinese formula Zi Huang Huo Xiang San (ZHHXS) modulates gut microbiota under heat stress, a heat stress model was prepared in Roman laying hens by housing them at temperatures of 32 36℃ and administering ZHHXS for four weeks. Gut microbiota in the hens’ feces was assessed through 16S rRNA high-throughput sequencing at days 1, 3, 7, 14, and 28. This study showed that the composition of gut microbiota in laying hens with heat stress was modulated by ZHHXS treatment. ZHHXS treatment caused key phylotypes of gut microbiota to match the BC group, particularly Actinobacteria, Bacteroidetes, Bacteroides, and Enterococcus. The effect of ZHHXS in alleviating heat stress could be achieved by altering the composition of gut microbiota and regulating some key phylotypes.